2008
DOI: 10.1210/en.2007-1747
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Targeted Metabolomics—Uncovering Old and New Tales of Diabetic Mice under Medication

Abstract: Metabolomics is a powerful tool for identifying both known and new disease-related perturbations in metabolic pathways. In preclinical drug testing, it has a high potential for early identification of drug off-target effects. Recent advances in high-precision high-throughput mass spectrometry have brought the metabolomic field to a point where quantitative, targeted, metabolomic measurements with ready-to-use kits allow for the automated in-house screening for hundreds of different metabolites in large sets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 30 publications
7
97
0
Order By: Relevance
“…As shown previously, the use of such ratios leads to a strong reduction in the overall variance and therefore improves the strength of association [13]. A high increase in the strength of association may also indicate that the two metabolites are linked by a metabolic pathway that is influenced by the respective (nutrition) factor.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As shown previously, the use of such ratios leads to a strong reduction in the overall variance and therefore improves the strength of association [13]. A high increase in the strength of association may also indicate that the two metabolites are linked by a metabolic pathway that is influenced by the respective (nutrition) factor.…”
Section: Discussionmentioning
confidence: 64%
“…The technique is described in detail in [27,28] published by the FDA (Food and Drug Administration), which implies proof of reproducibility within a given error range. This measurement platform has been successfully used in the past in different academic and industrial applications [12][13][14].…”
Section: Metabolite Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants that affect the efficiency of a specific enzyme should be best reflected in the ratio of this enzyme's relative substrates and products rather than in the absolute concentration of either of them. This metabolite ratio approach was introduced by Altmaier et al (2008), and its utility was demonstrated by a pronounced increase in the strength of the association that was observed for FADS1. Here, changes in the catalytic activity of FADS1 due to its polymorphism may alter the levels of eicosatrienoyl-CoA (C20:3) and arachidonyl-CoA (C20:4), which in turn translates into changes on the PC 36:3 and PC 36:4 concentrations.…”
Section: Targeted Metabolomic Phenotypes In Gwasmentioning
confidence: 99%
“…MS has been now established as the stateof-the-art analytical tool in which richest data from molecular systems can be acquired. In medicinal chemistry, three MS approaches might be highlighted as the most prominent: data dependent UPLC-ESI-HRMS metabolomics [3], data dependent nanoLC-nanoESI-HRMS proteomics [4] and MS imaging applied to the biomarker screening of tissues [5].Metabolomic MS screening can usually be categorized into untargeted [6] and targeted analysis [7]. In untargeted metabolomics, as many molecules as possible are identified in a sample.…”
mentioning
confidence: 99%